Sosialisasi Pentingnya Pelayanan Prima Pada Komsumen Untuk Pertumbuhan Perusahaan - Muhammad Asyari Syahab; Aprilda Yanti (Jurnal Pengabdian Masyarakat Eka Prasetya, 2023)
In this modern century, the development of Science and Technology is increasingly advanced. This encourages the development of the business world to become increasingly rapid and market competition increasingly fierce, thus requiring an increasingly better marketing system for every company operating in the field of products and services. Marketing is one of the means for companies to achieve the goals set by the company. In order for this goal to be achieved, every company must strive to produce and deliver goods or services that consumers want by providing good service and supporting facilities.. Customers always expect excellent service so that they feel satisfied. Apart from that, the benefits of providing excellent service include improving the quality of company or government services which makes it a daily operational standard.